A Systematic Literature Review of Problem-Based Learning in Chemistry Education: Advancing Critical Thinking and Motivation - Ira Nurpialawati; Das Salirawati (Jambura Journal of Educational Chemistry, 2026)
This systematic review evaluates the directional trends, pedagogical benefits, and execution challenges of Problem-Based Learning (PBL) within chemistry education over the past five years, emphasizing its impact on student motivation and critical thinking. Operating via a Systematic Literature Review (SLR) anchored in the PRISMA framework, this study synthesizes recent empirical data. The findings reveal a pronounced upward trajectory in PBL adoption, particularly accelerating after 2020. Empirically, the model consistently advances critical thinking, analytical reasoning, problem-solving, and scientific argumentation, while concurrently elevating academic achievement and laboratory performance. It also refines student research skills, scientific attitudes, and creative thinking. Concurrently, PBL substantially amplifies learning motivation, evidenced by heightened student interest, engagement, positive attitudes, and readiness. However, certain cases show that advancements in motivation and problem-solving do not always significantly surpass alternative instructional methods, highlighting the influence of contextual variables. Practically, implementation frequently relies on innovative modules like E-LKPD and e-modules, collaborative frameworks, technology, and structured scaffolding. Conversely, prominent challenges persist, including scarce target materials, varying facilitator capacity, learner resistance, and resource limitations. By consolidating empirical insights into how PBL mediates critical thinking and motivational growth, this inquiry enriches constructivist theory in chemistry pedagogy and delivers an integrative model for 21st-century education. While PBL remains a valuable pedagogical strategy, its successful deployment necessitates sustained professional development for educators alongside deeper exploration into its interplay with student learning styles and technology integration across diverse contexts.